Pengaruh Kepemimpinan Transformasional Dan Motivasi Kerja Terhadap Kinerja Pegawai Di Dinas Pemberdayaan Masyarakat Dan Desa (DPMD) Kabupaten Bone Bolango - Patingki, Windi Angriyani (JPS: Journal of Publicness Studies, 2026)
Motivation is the driving force behind a person's participation in a specific activity; it is frequently thought of as the driving factor behind a person's behavior. The following are the study's objectives: (1) To ascertain whether employee performance at the DPMD of Bone Bolango Regency is impacted by transformational leadership. (2) To find out whether work motivation affects the performance of staff services at the DPMD of Bone Bolango Regency. (3) To find out whether transformative leadership and work motivation affect employees at the DPMD of Bone Bolango Regency simultaneously. The methodology of this study is correlational and quantitative. The third has functioned satisfactorily but not optimally, according to the research findings: With a score of 76.49% for work motivation, 80.72% for staff performance, and 75.59% for transformative leadership, this is included in the quite extraordinary group. The three have functioned satisfactorily but not optimally, according to the investigation findings: With a score of 76.49% for work motivation, 80.72% for staff performance, and 75.59% for transformative leadership, this is included in the quite extraordinary group. Statistically, work motivation has an influence of 45.70%, transformative leadership has a beneficial and significant impact on performance of 25.90%, and both have an impact of 71.60%. Other factors not examined impacted the remaining 28.40%. Employee performance at the Bone Bolango Regency DPMD will improve along with improved leadership and increased work motivation.